Secular trends in height and weight among children and adolescents of the Seychelles, 1956-2006 - Romain Sarah; Madeleine George; Marques-Vidal Pedro; Gabriel Anne; Bovet Pascal (BMC, 2008)
Abstract Background Height of individuals has long been considered as a significant index of nutrition and health of a population; still, there is little information regarding the trends of height and weight among developing or transitional countries. We assessed the secular trends in height and weight in children of the Seychelles, a rapidly developing island state in the Indian Ocean (African region). Methods Height and weight were measured in all students of all schools in four selected school grades (kindergarten, 4th, 7th and 10th grades) for the periods 1998-9 (6391 children) and 2005-6 (8582 children). Data for 1956-7 was extracted from a previously published report. Results At age 15.5 years, boys/girls were on average 10/13 cm taller and 15/9 kg heavier in 2005-6 than in 1956-7. Height increased in boys/girls by 1.62/0.93 cm/decade between 1956-7 and 1998-9 and by 1.14/1.82 cm/decade between 1998-9 and 2005-6. For weight, the linear increase in boys/girls was 1.38/1.10 kg/decade between 1956-7 and 1998-9 and 2.21/2.50 kg/decade between 1998-9 and 2005-6. Overall, the relative increase in weight between 1956-7 and 2005-6 was 5-fold higher than the relative increase in height. Conclusion Height and weight increased markedly over time in children aged <16 years in the Seychelles, consistent with large changes in socio-economic and nutritional indicators in the considered 50-year interval. The markedly steeper increase in weight than height over time is consistent with an epidemic of overweight and obesity.